How do you differentiate y = (1 + cos^2x) / (1 - cos^2x)y=1+cos2x1cos2x?

2 Answers
Jun 5, 2015

One thing you can do is use some identities so that you can avoid overcomplicating it and having to simplify the results of the quotient rule.

sin^2x + cos^2x = 1sin2x+cos2x=1

so

1+cos^2x = 1+(1-sin^2x) = 2-sin^2x1+cos2x=1+(1sin2x)=2sin2x
1-cos^2x = sin^2x1cos2x=sin2x

and so

(1+cos^2x)/(1-cos^2x) = (2-sin^2x)/(sin^2x) = 2/(sin^2x) - 11+cos2x1cos2x=2sin2xsin2x=2sin2x1

= 2csc^2x - 1=2csc2x1

(df(x))/(dx) = 2[2cscx*-cscxcotx] = -4csc^2xcotxdf(x)dx=2[2cscxcscxcotx]=4csc2xcotx

An alternate form of this from Wolfram Alpha is:
-(16cosx)/(3sinx-sin3x)16cosx3sinxsin3x

but the accepted answer on Wolfram Alpha is the first one, -4csc^2xcotx4csc2xcotx.

Jun 6, 2015

I would rewrite the function:

y=(1+cos^2x)/(1-cos^2x) = (1+cos^2x)/sin^2xy=1+cos2x1cos2x=1+cos2xsin2x

= 1/sin^2x + cos^2x/sin^2x=1sin2x+cos2xsin2x

=csc^2x + cot^2x=csc2x+cot2x

Now differentiate using the chain ruloe and the derivatives of cscxcscx and cotxcotx:

y' = 2cscx(-cscxcotx) + 2 cotx(-csc^2x)

= -2csc^2xcotx-2csc^2xcotx

= -4csc^2xcotx.